Experience-dependent maternal defense behavior mediated by profrontal cortical projections to the medial preoptic area in mice - Kaibin Wu; Peiwen Tang; Yuwei Wang; Fangcai Mai; Yidi Pan; Li I. Zhang; Huizhong W. Tao; Feixue Liang (Nature Communications)
Abstract Maternal defense, a hallmark of motherhood, often involves protecting offspring at personal risk. However, the neural mechanisms underlying the emergence and modulation of this behavior remain not-well understood. Here, we introduce a novel paradigm in which mother mice under threat prioritize offspring protection over self-preservation by approaching, collecting, and retreating pups to safety, a risk-associated behavior that also develops in virgin females following maternal experience. Microendoscopic calcium imaging reveals sequential activation of distinct corticofugal neuronal populations in the medial prefrontal cortex (mPFC) during maternal defense. Specifically, layer (L)6 dopamine receptor D1-expressing (D1) neurons are active during pup approach, while L5 neurons are engaged during pup collection and retreat. Activation of the L6 neurons bidirectionally modulates maternal defense via projections to the medial preoptic area. These findings suggest that mPFC L6 D1 neurons may facilitate the transition to maternal behavior by influencing behavioral selection and initiating maternal defense response under threat.